2022
DOI: 10.3390/cancers14020335
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13C-Pyruvate Metabolism as a Surrogate for Tumor Grade and Poor Outcome in Renal Cell Carcinoma—A Proof of Principle Study

Abstract: Differentiating aggressive clear cell renal cell carcinoma (ccRCC) from indolent lesions is challenging using conventional imaging. This work prospectively compared the metabolic imaging phenotype of renal tumors using carbon-13 MRI following injection of hyperpolarized [1-13C]pyruvate (HP-13C-MRI) and validated these findings with histopathology. Nine patients with treatment-naïve renal tumors (6 ccRCCs, 1 liposarcoma, 1 pheochromocytoma, 1 oncocytoma) underwent pre-operative HP-13C-MRI and conventional proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…9 This is also evidenced by the adoption of spiral-based Dixon methods, which essentially consist of the acquisition of an extremely concise spectrum. 158,159 For sodium imaging, because of the short biexponential T 2 relaxation, UTE was recommended to acquire the images in three dimensions with a nonselective hard excitation pulse. 160 3D multiecho radial imaging offers an efficient 23 Na multiparameter tissue compartment mapping that extends regular 23 Na imaging.…”
Section: Acquisition Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 This is also evidenced by the adoption of spiral-based Dixon methods, which essentially consist of the acquisition of an extremely concise spectrum. 158,159 For sodium imaging, because of the short biexponential T 2 relaxation, UTE was recommended to acquire the images in three dimensions with a nonselective hard excitation pulse. 160 3D multiecho radial imaging offers an efficient 23 Na multiparameter tissue compartment mapping that extends regular 23 Na imaging.…”
Section: Acquisition Techniquesmentioning
confidence: 99%
“…This is probably because clinical scenarios usually have determined targeting metabolites, making the nonspectroscopic readout techniques more time‐efficient for clinical scenarios 9 . This is also evidenced by the adoption of spiral‐based Dixon methods, which essentially consist of the acquisition of an extremely concise spectrum 158,159 …”
Section: Mn Mri/mrs Techniquesmentioning
confidence: 99%
“…Several clinical reports have shown the potential of HP- 13 C-MRI to detect PCa, assess disease aggressiveness, and detect tumour response to therapy [2][3][4][5][6][7] . Importantly, some of these studies have attempted to explain the mechanism of the observed tumour [1- 13 C]lactate labelling patterns by correlating imaging data with tissue-based metabolic biomarkers 2,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical reports have shown the potential of HP- 13 C-MRI to detect PCa, assess disease aggressiveness, and detect tumour response to therapy 27 . Importantly, some of these studies have attempted to explain the mechanism of the observed tumour [1- 13 C]lactate labelling patterns by correlating imaging data with tissue-based metabolic biomarkers 2,810 . However, a more comprehensive biological validation of HP- 13 C-MRI is required to assess its translational potential and navigate its use in specific clinical scenarios 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperpolarized (HP) 13 C‐labeled MRI has shown its ability to investigate Smetabolic processes in vivo. In current clinical research, HP [1‐ 13 C]pyruvate MRI has been applied in human brain tumor studies, 1,2 prostate cancer studies, 3,4 cardiac studies, 5–7 breast cancer studies, 8 pancreatic cancer studies, 9 and renal cell carcinoma (RCC) studies 10,11 …”
Section: Introductionmentioning
confidence: 99%